The land before time - Gwynne, Fred.; Bluth, Don.; Amblin Entertainment (Firm); Universal Pictures Company; MCA Universal Home Video (Universal City, CA : MCA Universal Home Video, 1996)
Littlefoot, a young brontosaurus, sets off on a journey in search of the Great Valley where dinosaurs can live in peace and safety. On this amazing journey, he meets four other young dinosaurs and they have incredible adventures.
Rated G.
Closed captioned for the hearing impaired.
Animation.
Video cassette release of the 1988 motion picture.
In hi-fi, stereo. surround, Dolby processed.
"This film has been modified from its original version; it has been formatted to fit your TV.
Keywords: Dinosaurs -- Juvenile fiction; Animated films; Children's films; Dinosaurs -- Juvenile films; Video recordings for the hearing impaired